Polanyi and Schumpeter vs. Neoliberalism: Can Neoliberal World Be Explained by Schumpeter in the Context of Innovation and Polanyi in the Context of the Market? - Akansel, Ilkben (Handbook of Research on Managerial Thinking in Global Business Economics, 2019)
Neoliberalism means “new liberalism.” It could be dated back to 18th century, but it is a term that belongs today. Since 1990, neoliberal rules gave many harmful effects, especially to developing countries, and those harmful effects have proceeded for labor class. As capitalism stands on its own feet, it can find solutions to regain profits. However, the concern may well be gaining too much profit gives harmful effects on a wide range of social classes. Neoliberalism is accepted as the tool of these effects by the majority of the economists. In this chapter, the authors scrutinize the consequences of neoliberalism by the mediation of two great philosophers who criticized capitalism in different ideas. Karl Polanyi's and Joseph A. Schumpeter's different opinions about capitalism will be scrutinized in order to understand the connection between capitalism and neoliberalism. So, in this study, starting with its name, neoliberalism's implementations will be scrutinized by two great philosophers
Economics
Keywords: business economics; neoliberalism

Karl Polanyi vs Friedrich von Hayek: The Socialist Calculation Debate and Beyond - Dale, Gareth (Hayek: A Collaborative Biography: Part XIV: Liberalism in the Classical Tradition: Orwell, Popper, Humboldt and Polanyi, 2018)
It is well known that Friedrich von Hayek’s The Road to Serfdom and Karl Polanyi’s The Great Transformation were written contemporaneously (between 1940 and 1943), that their authors propounded antithetical political ideologies (right-wing liberalism and left social democracy respectively), and that the two books revolve around a similar problematique: the causes of the collapse of liberal order in the interwar era. This chapter undertakes a detailed comparison of Hayek and Polanyi’s Weltanschauung (including ethics, economic analysis, and political perspectives). It reveals a chequered picture, in which diametrically opposed political views articulate with points of striking agreement in economic analysis. This helps to explain the manner in which certain Polanyian theses, notably on the ‘constructed’ market order and the ‘spontaneous’ social-movement response, appear to mirror those of Hayek.
Biography; History; Economics
Keywords: Great Transformation; The (Book); HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Polanyi; constructed market order; history of economic thought; liberalism; methodology; socialist calculation debate

Adventures of an Austrian Trio Abroad: The Influence of Schumpeter, Polanyi and Hayek in Turkey and the Dissemination of Their Work - Ozveren, Eyup (The Dissemination of Economic Ideas, 2011)
Economics
Keywords: Austrian; Keynesian; Keynesianism; evolutionary; general aggregative models: Keynes; history of economic thought; history of economic thought since 1925: historical; history of economic thought: individuals; institutional; post-Keynesian; role of economics; role of economists

From Menger to Polanyi: The Institutional Way - Cangiani, Michele (Austrian Economics in Transition, 2010)
The crisis of the institutions of liberal capitalism dates back to the last decades of the nineteenth century. Economics was thenceforth forced to radically reconsider its achievements and even its basic presuppositions, to the extent that they were linked to a free-market and perfect-competition model.
History; Economics
Keywords: economic history; economic systems; economic theory; financial economics; history of economic thought; international economics; macroeconomics; mathematical methods; methodology; monetary economics; quantitative economics

The Financialization of Modern Economies in Monetary Circuit Theory - Pilkington, Marc (The Political Economy of Monetary Circuits: Tradition and Change in Post-Keynesian Economics, 2009)
Economics
Keywords: Canada: 1913-; banks; depository institutions; economic history: financial markets and institutions: United States; government and the monetary system; haute finance; history of economic thought: individuals; household saving; international financial markets; micro finance institutions; monetary policy; central banking; and the supply of money and credit; monetary systems; mortgages; payment systems; personal finance; regimes; standards

Where Does the Market Come From? Why the Controversy Between Polanyi's "Substantivists" and "Formalist" Neoclassical Protagonists of a Universal Market Was Never Solved" - Heinsohn, Gunnar (Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy, 2008)
In Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy - Metropolis-Verlag, 2008.
Sociology; Economics
Keywords: formalist; substantivist

Third Sector, Social Economy, Civil and Solidarity-Based Economy: European Reality and Theoretical Debate | - Laville, Jean-Louis (2008)
This is a book chapter from: The Social Generative Action of the Third Sector – Comparing International Experiences Edited by H. K. Anheier; G. Rossi, L. Boccacin, 2008, Vita e Pensiero, Milano
Sociology; Economics
Keywords: social economy; solidarity economy

The Slight Transformation: Contesting the Legacy of Karl Polanyi - Lacher, Hannes (Reading Karl Polanyi for the Twenty-First Century, 2007)
The postwar reconstruction of domestic and international orders ushered in a new political economy of capitalism. It entailed a far-reaching reorganization of social relations and economic institutions and accorded to the state an important role in the management of the economy. Many of the institutions of classical liberalism were displaced by interventionist mechanisms. The welfare state consolidated and extended multifarious forms of protection accorded to labor. A new level of labor-market regulation and public provisioning transformed the conditions under which people worked and lived, leading to higher incomes for large groups of society, and creating a higher degree of security for them both in the workplace and beyond. International institutions were created to facilitate the regulatory functions that these welfare states had assumed, supported by a conducive exchange-rate regime and restrictions on capital mobility.
Political Science; Economics
Keywords: capital mobility; market society; market system; postwar period; postwar reconstruction; welfare state

Karl Polanyi on the Limitations of Formalism in Economics - Stanfield, James Ronald; Carroll, Michael C.; Wrenn, Mary V. (Choice in Economic Contexts, 2006)
This chapter examines Karl Polanyi's critique of formalism in economics and his case for a more institutional economics based upon a reconstitution of the facts of economic life on as wide an historical basis as possible. The argument below reviews Polanyi's argument with regard to the relation between economic anthropology and comparative economics, the contrast between the formalist and substantive approaches to economic analysis, the notion of an economistic fallacy, the most important limitations of the conventional formalist economics approach, and the nature and import of the new departure that Polanyi envisioned. James Ronald Stanfield, Michael C. Carroll, Mary V. Wrenn (2006), Karl Polanyi on the Limitations of Formalism in Economics, in Donald C. Wood (ed.) Choice in Economic Contexts (Research in Economic Anthropology, Volume 25) Emerald Group Publishing Limited, pp.241 - 266
Economics; Anthropology
Keywords: economic anthropology; formalism

Karl Polanyi as a Development Economist - Polanyi Levitt, Kari (Pioneers of Development Economics: Great Economists on Development, 2005)
The history of modern economic thought has been pre-occupied with the question of economic transformation or development. This survey of important contributions to the economics of development includes many economists not normally considered as pioneers in this field. The contributors point to the role of imperialist considerations in the early development of economic thought and the development discourse, and the impact of pressures for social and political reform. The economists and thinkers discussed include William Petty, David Ricardo, Friedrich List, Alexander Hamilton, Karl Marx, Vladimir Ilyich Lenin, Alfred Marshall, Michal Kalecki, John Maynard Keynes, Nicholas Kaldor, Karl Polanyi, Raul Prebisch, Arthur Lewis, Alexander Gerschenkeron and Hans Singe
Economics
Keywords: development economics; economic history

Economic Rationality and Globalization: A Feminist Perspective - Beneria, Lourdes (Feminist Economics Today: Beyond Economic Man, 2003)
KM: a section focuses on Polanyi's analysis of the social and political construction of markets and of "market society" in Europe, and then discusses the extent to which this type of analysis can be applied to the formation of global markets in the late twentieth century. It then looks at gender dimensions and the tension between the assumptions of economic rationality associated with market behaviour and the real-life experiences of women and men. Beneria then extends this analysis to the effects on women of globalization and the feminization of the labour force.
Economics
Keywords: feminism; feminization of labour force; gender; globalization; market society

Karl Polanyi's Great Transformation and the Current Transformations in Central Europe - Hake, Eric R.; Neale, Walter C. (Economic transition in historical perspective: Lessons from the history of economics, 2001)
Economics
Keywords: agriculture; collectives; communes; comparison of public and private enterprises and nonprofit institutions; contracting out; economic thought; history of economic thought: individuals; illegal behavior; legal institutions; nonprofit institutions; privatization; public enterprises; socialist systems and transitional economies: legal institutions; transitional economies

Groundwork for an Institutional Economic Approach to 'Transition': Smith and Polanyi Reconsidered - Ozveren, Eyup (Economic transition in historical perspective: Lessons from the history of economics, 2001)
Economics
Keywords: Marxist; SMITH; Adam; 1723-1790; current heterodox approaches: institutional; evolutionary; history of economic thought; history of economic thought through 1925: socialist; history of economic thought: classical; history of economic thought: individuals; socialist systems and transitional economies: performance and prospects P27

Polanyi and social economy - Isaac, Barry L. (A Handbook of Economic Anthropology, 2022)
Substantivism stemmed from the writings of Hungarian lawyer-turned-historian Karl Polanyi, who argued that capitalism is a historically unique kind of economy that is disembedded from the social matrix. By implication, the socially embedded pre-capitalist economies studied by anthropologists, historians and classicists cannot be understood using the formal economics developed to analyze capitalist economies. Rather, new tools for analysing their 'substantive' economies must be employed. Substantivism was championed in economic anthropology by economist-turned-anthropologist George Dalton and became the reigning paradigm in the subfield during the 1960s. Formalism arose in opposition, arguing that capitalist and pre-capitalist economies differ in degree, not in kind, and thus can all be analysed using the tools of microeconomics. Formalism largely displaced substantivism during the 1970s and 1980s as anthropologists increasingly focused on the economic integration of the world's peasant sectors into their national and regional economies.
Economics; Anthropology

Market society and the institutional theory of Karl Polanyi - Cangiani, Michele (Institutional Economics: Perspectives and Methods in Pursuit of a Better World, 2021)
This chapter examines Polanyi’s institutional theory of market-capitalist society. It shows that market society is, according to Polanyi, a peculiarly “economic” society: its economy appears both autonomous and dominant, constraining the structure and evolution of other social subsystems. The chapter also demonstrates that Polanyi’s theory and method allow an explanation of the institutional transformations of market society. In the face of today’s great economic difficulties, social uneasiness, and ecological distress, Polanyian institutionalism remains a rich source of insight on humanity’s challenges and possibilities.

This freedom kills: Karl Polanyi’s quest for an alternative to the liberal vision of freedom - Brie, Michael (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reconstructs the emergence and formulation of Karl Polanyi's central research question: How is responsible freedom possible in a complex modern society? The origins of this question in the time before the First World War and the confrontations with the challenge of neoliberalism and fascism are discussed. It is shown that Karl Polanyi's concept of freedom has four dimensions. Polanyi connects negative, positive, substantial and social freedom with each other and formulates a highly innovative research programme which forms the basis for The Great Transformation and later works.
Sociology; Economics
Keywords: freedom; freedom in a complex society

Double movement, embeddedness and the transformation of the financial system - Galarza, Oscar Ugarteche (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reviews aspects of the possible transformation of the financial system into a banking complex, that comprises both embedded Too Big to Fail (TBTF) financial institutions and disembedded ones. The transformation of the financial system into a two-tier banking complex is the result of the disconnection of the TBTF embedded institutions and the right size to fail disembedded financial institutions. The chapter revises the scope and consequences of this change on the monopolization of financial capitalism and international financial governance. It contains two sub-sections. The first reviews Polanyi’s concept of embeddedness/ disembeddedness and TBTF; the second reviews the concept of a complex. This chapter aims to use Polanyi’s concept of embeddedness and disembeddedness in order to understand how the category of TBTF financial institutions came into being through the double movement of market deregulation and social regulation. The concepts of embeddedness in social regulation and disembeddedness under market regulation permit an understanding of how, as the few TBTF financial institutions re-embedded themselves, becoming risk proof, the majority remained disembedded and subject to failures. We argue that, given this, the financial system may no longer be considered a system.
Economics; Political Science
Keywords: disembeddedness; double movement; embeddedness; financial system; too big to fail